RANCANG BANGUN MESIN PENGHANCUR ARANG TEMPURUNG KELAPA - Yoga Alvero; Iswanto; Cindy Vena Ariesta; Muhammad H Amrullah; Pristiansyah Pristiansyah (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Bangka Belitung Province is possible to increase the selling value of charcoal by utilizing coconut shell waste as charcoal fuel, especially in the Bangka area, Sungailiat District. To increase the selling value of charcoal, many SME (small and medium enterprises) actors use charcoal to make charcoal bricks. This can be seen in the briket production process at the marketing and community levels. In summary, it is necessary to make charcoal briket presses, especially charcoal crushers. The existence of a coconut shell charcoal crusher machine can speed up the brick production process and produce good quality bricks. The purpose of this research is to design and manufacture a coconut shell charcoal crusher using the VDI 2222 research method to produce a coconut shell charcoal crusher with a possible effective capacity of 10 kg/10 minutes, which can be carried out continuously and produces an output of 4.5 kg in one process, and produce charcoal granules with a maximum size of 2 mm.